Analisis Kesulitan Belajar Matematika SD Ditinjau dari Kemampuan Literasi Numerasi - Fitria, Siti Wulan; Tisngati, Urip; Fath, Ayatullah Muhammadin Al (Scholarly Journal of Elementary School, 2021)
This study aims to determine: (1) student’s numeracy literacy skills, (2) students’ mathematics learning difficulties, and (3) mathematics learning difficulties in terms of numeracy literacy skills in 4-grade students at SDN Ngadirejan.This type of research was descriptive qualitative. The results have shown that: (1) the grade 4 students of SDN Ngadirejan had high numeracy literacy skills as many as 16%, of students with a moderate level of numeracy literacy skills as many as 20%, of students with a moderate level of numeracy literacy skills as much as 24%, and 40% of students with low-level numeracy literacy skills; (2) Types of learning difficulties in mathematics experienced by grade 4 students at SDN Ngadirejan were weaknesses in calculating, difficulty in transferring knowledge, poor in an understanding of mathematical language, and difficulty in visual perception. (3) The difficulties in learning mathematics in terms of students' numeracy literacy abilities showed differences in each category. The higher the numeracy literacy ability, the smaller the difficulties experienced by students.